Review of Risk Management Implementation in the Filing Room at Griya Husada Hospital, Madiun - Rahmaputri Ardianingrum, Al Wafi; Umianingsih , Sri; Devi Apriliani, Eltigeka (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2023)
Occupational safety priorities for filing staff at Griya Husada Hospital, Madiun require an assessment of risk factors in the filing room. Risk factors include physical, chemical, biological, ergonomic, stressor, document damage, and reputational factors in the filing room to minimize potential risks. The purpose of this study was to describe the implementation of risk management in the filing room at Griya Husada Hospital, Madiun. This study used qualitative methods with four informants. Data collection involved interviews and observations. The study concluded that physical risk factors included inadequate filling room temperature (29°C), misfiled files; ergonomic risk factors included back and neck pain; stressor fatigue; and torn document covers. The room temperature should be as comfortable as possible to maintain a normal temperature. Ventilation, including fans and exhaust, is essential for air circulation in the filling room to prevent stuffy and humid conditions. It is necessary to add a thermometer, create a plan, manage, and control risk management for implementation.